Prevention Of Drug Abuse In The Community Environment - Anggraini, Tia Ayu (Legalpreneur Journal, 2022)
Prevention of drug abuse, especially young people need to be made. remembering conditions in Indonesian society crime of use narcotics is not only done by adults, will but it is also practiced by children teenagers who are still in school. Thus, protecting the younger generation who are still in school become an obligation that can not be abandoned, either individual or society. On the one hand, there are already many thoughts and efforts made related to prevention of narcotics in question, starting from the program national who formed a special agency to handle narcotics (National Narcotics Agency) sanpai swadaya society. However, drug abuse is still occur in the community, including among children school. Therefore, an action is required preventive measures to stop drug abuse, especially in the community environment. These efforts have had an impact diniali positive for students. However, environmental conditions can be forcing them to fall into drug abuse, if controlan of various parties are not done.